The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c3cs60413f
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive assemblies of organic compounds and biomolecules: drug–protein supramolecular systems

Abstract: Modification of the drug excited state properties within proteins provides information on binding and may result in a different photoreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 159 publications
0
46
0
1
Order By: Relevance
“…In homogeneous aqueous solutions of PSA or chlorin the 1 O 2 lifetime has been determined as 3.5 µs, in accordance with the data reported for other photosensitizers [38]; such a low value reflects efficient quenching of singlet oxygen by water molecules. In the presence of HSA, however, the two examined systems behave quite differently; cf.…”
Section: Transient T-t Absorbance Of Psa and Singlet Oxygen Emissionmentioning
confidence: 91%
“…In homogeneous aqueous solutions of PSA or chlorin the 1 O 2 lifetime has been determined as 3.5 µs, in accordance with the data reported for other photosensitizers [38]; such a low value reflects efficient quenching of singlet oxygen by water molecules. In the presence of HSA, however, the two examined systems behave quite differently; cf.…”
Section: Transient T-t Absorbance Of Psa and Singlet Oxygen Emissionmentioning
confidence: 91%
“…12 Stereodifferentiation in the triplet lifetimes of ligands within transport proteins has previously been observed in other cases, such as carprofen, flurbiprofen, flurbiprofen methyl ester or 2-anthracene propionic acid incorporated into serum albumins. 7c,14 …”
Section: Resultsmentioning
confidence: 99%
“…160 ms) was more than 500 times longer than that obtained for 3 COL* in acetonitrile (s ¼ 0.29 ms), which agrees well with the markedly longer triplet lifetimes usually measured in the intraprotein microenvironment. 43,44,63 Comparison of the decay traces of 3 COL* in acetonitrile and 3 COL*@TU in aqueous solutions revealed that the initial intensity of the signal immediately aer the laser pulse was higher in the organic solvent (Fig. 1, inset).…”
Section: Resultsmentioning
confidence: 99%
“…42 More recently, laser ash photolysis (LFP) has been introduced as a new tool to investigate drug-protein interactions and to determine binding parameters such as affinity constants or population of the binding sites. 43,44 Interestingly, the absence of a triplet excited state detectable in LFP has revealed that COL does not bind to serum albumins. 45 This technique is very sensitive and does not require separation of free and complexed drug.…”
Section: Introductionmentioning
confidence: 99%